DEVELOPMENT OF AMPLIFICATION REFRACTORY MUTATION SYSTEM PCR TO DETECT ANDROGEN RECEPTOR GENE G1773A (RS6152) POLYMORPHISM - Triyana Sari; Erick Sidarta; Sari Mariyati Dewi Nataprawira; Giovani Evangelista Alfonsius; Damar Sajiwo (Sean Institute, 2023)
Androgen receptor (AR) is a ubiquitous receptor responsible for responses by androgen stimulus. Androgen, a hormone which will bind to the AR, is essentials for normal male sexual development. Nevertheless, one of the polymorphisms in the AR gene, G1733A (rs6152) have been associated with numerous clinical risks such as cardiovascular disease (CD), androgenetic alopecia, high prostate-specific antigen (PSA) levels, male infertility, recurrent spontaneous abortions and prostate cancer. This study aims to develop an alternative and cost-effective method to detect G1773A (rs6152) polymorphism. In this study, amplification refractory mutation system-polymerase chain reaction (ARMS-PCR) using two pair of primers was used to detect the G1733A (rs6152) polymorphism. Primer design was done using http://primer1.soton.ac.uk/primer1.html online tools and then manually adjusted to increase the specificity. A total of 54 samples were screened using ARMS PCR and 2 representative samples of each allele from previous screening were used to validate the results using Sanger DNA sequencing. Among 54 subjects screened, we found 52 (96.3%) subjects carry G allele and 2 (3.7%) subjects carry A allele. No heterozygote was found in this study. The frequency of G allele was 96.97% and the frequency of A allele was 3.03%. Result validation using DNA sequencing was in agreement with ARMS-PCR method results. ARMS-PCR can be used as efficient alternative for genotyping of G1733A (rs6152) AR gene polymorphism